The necessity of systematization of normative documents on the prevention of crime - Khujakulov, Siyovush (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article substantiates the need to systematize normative documents on the prevention of offenses, based on the results of the analysis of scientific views of legal scientists, the practice of prevention of offenses and normative documents. Scientific conclusions and proposals for improving national legislation aimed at developing scientific and theoretical approaches to these issues have been developed. Scientific conclusions were made about the importance of systematization (codification) of normative legal acts on the prevention of offenses